A Multi-Centered Case Series Highlighting the Clinical Use and Dosing of Lidocaine and Mexiletine for Refractory Cancer Pain. (2nd April 2020) - Atayee, Rabia S.; Naidu, Dharma; Geiger-Hayes, Jessica; Saphire, Maureen L.; Hausdorff, John; Edmonds, Kyle P.
Abstract: Lidocaine infusion for pain control has been used for years. While some centers transition from continuous infusion lidocaine to oral mexiletine, there are no published studies to guide this conversion in pain and palliative care settings. This is a retrospective case series of 10 cancer patients across four institutions, with attention to dosing of both agents, and subsequent decrease in morphine-equivalent daily dosing (MEDD). The mean age was 55 years (range 34–78). The mean bolus dose of lidocaine was 1.6 mg/kg, infused over an average of 24 minutes, followed by a mean continuous infusion rate of 1.1 mg/kg/hr, and the infusion was continued for an average of 14.1 hours (range of 0.2 – 28 hours). The mean starting daily mexiletine dose was 400 mg (in 2–3 divided doses) and final dosing averaged 500 mg/day. The mean MEDD prior to starting lidocaine was 1118 mg/24 hours, which, by the time of final mexiletine dosing, was 882 mg/24 hours, a 21% MEDD reduction. The average hospital length of stay was 14 days. There was no lidocaine-induced toxicity and no lidocaine levels were obtained. Two of the 10 patients stopped mexiletine early, one from confusion four days after initiation of mexiletine, and the other after six weeks due to dizziness and visual changes. For cancer patients with suboptimal pain control on large doses of opioid, lidocaine infusion followed by oral mexiletine was well tolerated and effective.